Two new species of the genus Chersodromia Walker (Diptera: Hybotidae) from Southeast Asia - Shamshev, Igor; Grootaert, Patrick (Zootaxa, 2005)
Two new species of the genus Chersodromia Walker are described from mangroves of Singapore: C. nigripennis sp.n. and C. singaporensis sp.n. Palpal sensory pits are recorded for the first time in the genus and Tachydromiinae as a whole. They are present in both species. Some aspects of the male terminalia in Chersodromia are shortly discussed.